The pharmacist facing the logistics of safely dispensing, storing and preserving drugs in healthcare units - Maria Josep Cabañas; Maria Queralt Gorgas (Farmacia Hospitalaria)
In response to the SARS-CoV-2 pandemic, the Hospital Pharmacy Services have quickly adapted to respond to a critical situation characterized by the constant and continuous admission of patients with severe pneumonia who needed treatment, requiring a transformation of the hospital in order to increase the number of hospital and critical beds. Moreover, other out-ofhospital spaces have been transformed into hospitalization units to absorb the large number of patients that had to be treated and isolated. To guarantee the distribution of medicines and the quality of the pharmaceutical care, drug distribution systems, such as unit dose and automated dispensing systems, have undergone transformations. Standard stocks were assigned for COVID units, and different dispensing circuits to avoid the risk of cross-contamination between COVID and non-COVID units were created, as well as disinfection protocols for medication transport systems and medication return protocols. All this without forgetting COVID treatment protocol’s changes that were affected by the availability of the drugs. The increase in the number of beds in out-of-hospital spaces, such as field hospitals, hotels, socio-medical centers and nursing homes, has challenged Pharmacy Services, since new medication dispensing and conciliation circuits have been created forcing the increase of pharmacy staff’s presence and modifying work shifts, to afford all the new tasks successfully. Development of contingency plans for the different Pharmacy Service activities and providing fluent communication channels are key elements for crisis situations or health emergencies such as the current pandemic.